Autosterilization Effect of Gamma Radiation in Non-sterile Radiopharmaceuticals - Widyastuti Widjaksana; Enny Lestari; Maskur Maskur; Sudarsih Sudarsih (3BIO: Journal of Biological Science, Technology and Management, 2022)
Gamma radiation is commonly used in sterilizing various products because of its microbial-killing property. Several radiopharmaceuticals are processed aseptically, which requires a well-managed GMP-based facility. This study aims to ensure that radiopharmaceutical can behave as an auto sterilizing agent since it contains radionuclide that emits gamma radiation. Sm-153-ethylenediaminetetramethylenephosphonate (Sm-153-EDTMP) and I-131-Hippuran were used as models in this study, in which various radioactivities of these products were added into non-sterile vials in the non-aseptic working area and tested for sterility using direct inoculation method. The result showed that samples containing 7 mCi of Sm-153-EDTMP and less than 2 mCi of I-131-orthoiodohippurate (I-131-Hippuran) changed the clarity of the media, but not for those containing higher radioactivity. The results showed that Sm-153-EDTMP and I-131-Hippuran at certain radioactivity can auto sterilize themselves, whereas the positive control sample and the products diluted with non-sterile water remained unsterile. This study showed that radiopharmaceuticals have auto sterilizing properties at relatively low radioactivity, depending on the products’ bioburden. Therefore, the usual aseptic preparation of some radiopharmaceuticals can be considered terminal sterilization.